Contexts, Forms and Outcomes of Mathematics Teacher Collaboration - Esteley C; Huang R; Mellone M; Soto G; Eden R; Coles A (Springer, 2024)
This open access book is the product of an international study which offers a state-of-the-art summary of mathematics teacher collaboration with respect to theory, research, practice, and policy.